Analisis Kritis terhadap Berbagai Tantangan Organisasi Bisnis di Era Global dan Strategi Mengatasinya (Jurnal Manajemen dan Ekonomi (JME), 2024)
There are many challenges faced by business organizations in this global era. Among them are the challenges of using the latest technology, social responsibility, and business ethics. Apart from that, there are also challenges in the form of global competition, human resource management, and consumer behavior challenges. Lastly, which is no less important, is the challenge of business organizations in trying to play a role in overcoming unemployment. All these challenges must be faced with strategies that suit the needs and developments of the times. The strategies used to face and overcome challenges should also be efficient and effective so that the goals of the business organization can be realized in accordance with previously prepared plans.This challenge must be faced by business organizations because it is a real challenge that cannot be avoided. By facing and overcoming these challenges, business organizations can achieve progress. Challenges become a means to improve the quality of products and services provided. Without challenges, business organizations will not achieve meaningful progress.
Keywords: challenges, business organization, strategy